Measuring attitude toward lucid dreams: a six-item scale - Schredl, Michael; Rieger, Janina; Göritz, Anja (Dreaming, 2019)
In recent years, the interest in lucid dreaming (dreaming with the conscious knowledge that one is dreaming) was stimulated by blockbuster films like 'Inception' and the media interest in studies indicating that lucid dreaming can be beneficial. However, systematic studies regarding the attitude toward lucid dreams are lacking. An online survey was completed by 1,380 persons (777 women and 603 men), whose mean age was 51.63 ± 14.13 years. The six-item scale measuring attitude toward lucid dreams showed high internal consistency. The attitude toward lucid dreams was highly correlated with the general attitude toward lucid dreams and decreased with age; women reported a more positive attitude. However, the attitude toward lucid dreams was markedly lower than the attitude toward dreams in general. It would be interesting to study what the bases of the attitude toward lucid dreams are, for example, information in the media, personal experience, and reports of friends. (PsycINFO Database Record (c) 2019 APA, all rights reserved)